Mitochondrial apoptosis induced by MNAT1 in laryngeal squamous cell carcinoma cells reverses drug resistance - Ran An; Fan Yang; Yujian Teng; Yan Guo; Rui Zhao; Jing Cao; Yaohui Liu; Yue Wang; Pengyan Liu; Ming Liu; Linli Tian (Translational Oncology)
Background: Laryngeal squamous cell carcinoma (LSCC), the predominant histological subtype of laryngeal cancer with a poor diagnosis, requires further exploration of its molecular mechanisms and potential therapeutic targets. Methods: The expression of MNAT1 in LSCC was detected by western blotting and IHC. EDU analysis, colony formation assay, scratch assay, transwell assay and flow cytometry were used to detect cell proliferation, migration, invasion and apoptosis. The downstream genes of MNAT1 were predicted by RNA-seq. The interaction between MNAT1 and GDF15 was verified by Co-immunoprecipitation assay. The effect of MNAT1 on mitochondrial activity in LSCC cells was determined by ROS, JC-1, and lysosomal mitochondrial activity. The effect of MNAT1 and GDF15 on tumor growth of drug-resistant cells was evaluated in vivo. Results: MNAT1 was highly expressed in LSCC tissues. After MNAT1-knockdown, the proliferation, migration and invasion of LSCC cells were inhibited, the level of apoptosis was significantly increased, and the resistance to cisplatin was decreased. MNAT1 interacts with GDF15. MNAT1 affects cell proliferation, migration and invasion through GDF15, and further affects mitochondrial apoptosis through AMPK pathway. In addition, MNAT1-knockdown and GDF15-knockdown reduced the tumor growth rate and enhanced the sensitivity of cisplatin in vivo. Conclusions: MNAT1 promoted GDF15-mediated changes in AMPK pathway to affect mitochondrial apoptosis, which reveals the progression of LSCC and the mechanism of chemotherapy resistance, providing a new understanding of the mechanism of mitochondrial apoptosis and chemotherapy resistance in LSCC.